The Effect Of Ethanol Extract From Tuba Leaves (Derris Elliptica) On The Decrease In Blood Glucose Levels In Male White Mice - Mukhlis Sanuddin; Rahmadha Trifah; Siti Nurul Khoiriyah (CV. AFDIFAL MAJU BERKAH, 2026)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, caused by disturbances in insulin secretion, insulin action, or both. One alternative treatment option is herbal/traditional medicine made from natural ingredients. This study aimed to determine the effect of ethanol extract of Tuba plant leaves (Derris elliptica) on blood glucose levels in male white mice induced with alloxan. This study used an experimental method in which mice were induced with diabetes using a dose of 150 mg/kgBW alloxan for 3 days. The test animals were divided into 6 treatment groups, each consisting of five mice. Group I, the normal control, was given 0.5% Na CMC; group II, the negative control, was given alloxan and 0.5% Na CMC; group III, the positive control, was given alloxan and glibenclamide; while groups IV, V, and VI were given alloxan and tuba leaf ethanol extract at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW, respectively. Blood glucose levels were measured on days 1, 7, 14, and 21. The results showed that a 400 mg/kg body weight dose of tuba leaf ethanol extract significantly reduced blood glucose levels by 125.4 mg/dl and was almost as effective as glibenclamide. A dose of 400 mg/kg body weight was the optimal dose, producing significant effects while remaining safe for use.